Antiperiodic solutions for nth-order functional differential equations with infinite delay - Afonso, Suzete M. [UNESP] (2016)
In this work, we establish the existence and uniqueness of antiperiodic solution for a class of nth-order functional differential equations with infinite delay. The main tool in our study is the coincidence degree theory. An example is presented to illustrate the results obtained.